Meteorološko osiguranje kopnenog prometa - Gelo, Branko (Promet - Traffic&Transportation, 2012)
The paper deals with some basic aspects of meteorological service management as related to safety and smooth operation of surface transport (road, rail, postal, telecommunications, internal circulation, pipelines, funiculars, pavements and pathways) with reference to different problems regarding safety hazards, environmental protection, economy problems, time-tables and frequencies and transport industry. A review has been made of respective presentation and methods of forwarding given meteorological elements and aspects (reports, forecasts, maps) as required for surface transport with reference to traffic routes (climatological, synoptic-weather).